Physician’ attitudes to growth hormone replacement therapy in adults following pituitary surgery: Results of an online survey - Aishah Ekhzaimy (Thieme Medical and Scientific Publishers Pvt. Ltd., 2020)
Objective: The aim of this study was to evaluate physician attitudes and practices in the management of adult growth hormone deficiency (GHD) following pituitary surgery. Materials and Methods: An online questionnaire survey was sent to a sample group of physicians. Results: A total of 131 respondents provided usable responses. More than three quarters were senior physicians, with most practicing in tertiary care centers (73%). Four-fifths of the respondents see at least 1 to 5 patients with GHD following pituitary surgery per year. Seventy-four percent acknowledge the benefit in principle of growth hormone replacement therapy (GHRT) for patients with GHD after pituitary surgery. Most respondents (84%) would only consider GHRT for symptomatic patients. However, 16% stated that patients with GHD after pituitary surgery generally suffer from the side effects of GHRT. Forty-four percent said that the serum insulin-like growth factor-1 (IGF-1) level is the best screening test for assessing GHD after pituitary surgery but 57% of the respondents would use IGF-I levels, and 29% the insulin tolerance test (ITT), in patients with a documented deficiency in three pituitary axes. The main barriers to long-term GHRT use were that it requires injections (67%), and is costly with limited supply (61%). Other reasons not to use GHRT include an absence of GHD symptoms and apparent GHT ineffectiveness (44%), physician lack of familiarity with the medication (40%), and lack of adherence to available guidelines (38%). Conclusion: This survey addressed physician attitudes and practices in recognizing and treating GHD in adult’s post-pituitary surgery. Regional guidelines must be developed to help address/tackle these issues and assist physicians in understanding and treating this condition.